Hepatitis C virus‐associated indolent B‐cell lymphomas: A review on the role of the new direct antiviral agents therapy. Issue 4 (26th March 2021) - Mazzaro, Cesare; Dal Maso, Luigino; Visentini, Marcella; Ermacora, Anna; Andreone, Pietro; Gattei, Valter; Pozzato, Gabriele
Abstract: Several studies have suggested that hepatitis C virus (HCV) may be the causative agent of some B‐cell non‐Hodgkin lymphomas (B‐NHL). Several authors have demonstrated that pegylated interferon (Peg‐IFN) plus ribavirin (RBV) can revert indolent low‐grade B‐NHL by inducing HCV eradication. Presently, the combination therapy (IFN plus RBV) has been abandoned since the direct antiviral agents (DAAs) have shown very high efficacy in achieving sustained virologic response (SVR) (range: 95%–100%). This review analyzed DAAs efficacy in HCV‐associated indolent low‐grade NHL, providing a detailed literature review. Overall, 122 B‐cell NHL patients were treated with DAAs: complete/partial hematological response, particularly in those with marginal zone lymphoma, was obtained in most cases. Hematological response, obtained either with DAAs or IFN‐based therapy, was similar. Nonetheless, DAAs therapy showed better tolerability and higher SVR. A fraction of the patients, despite SVR, underwent hematologic relapse or progression. In these cases, a recovery treatment with immunotherapy, or chemoimmunotherapy, had to be planned. In conclusion, data obtained from published studies mostly agree that HCV eradication with DAAs should be considered as the first‐line treatment in HCV‐related NHL. In fact, the chronic viral stimulation of the immune system might be the primary pathogenic mechanism in disease development and progression.